Utilização do grão de café verde (Coffea arábica Catuaí Vermelho) como aromatizante na elaboração de uma cerveja lager - Luna, Larisse Karen Silva Santos (2022)
The green coffee bean (Coffea arábica Catuaí Vermelho) although it presented the lowest flavoring in beans for green coffee (Coffea arábica Catuaí Vermelho), can be used and had positive effects also researched. The work is to develop a lager beer flavored with green coffee beans and the objective is to evaluate the product sensorially and physicochemically at the end. The study started with the factorial design in the beers, elaborated through the Composite Rotational Design (DCCR) statistical matrix, having as variables (x1, x2) the time and days of independent development with the green coffee bean. The beers were prepared with an 8-day fermentation process with the commercial yeast Saccharomyces cerevisiae lager type, at 12°C. After primary fermentation, 0.43g was selected for development and factorial temperature design time variations. Sensory analysis was performed using a 9-point structured hedonic scale to evaluate a consumed product. The best grain sample was flavored with 0.43g of green coffee for 15 days at a temperature of 2.5°C. Then, the physical-chemical experiments of the beer aged with coffee for 15 days were carried out, resulting in a final °Brix 5.17 ± 0.09, pH 4.46 ± 0.00, Titratable acidity (ATT) 1.78 ± 0. 09, Reducing sugars (mg/mL) 1.94 ± 0.07, Total sugars (mg/mL) 17.69 ± 8.25, Color (EBC) 18.82 ± 0.22, Alcohol (%v/v ) 6.14 ± 0.1. From the results and chemical products consumed with the legislation, it can be studied that it is not additionally from the green coffee altered it is suitable for the consumption of chemical products, such as the presentation of aroma and pleasant and desirable to the, in addition to guaranteeing an innovation technology in the production process of beers with green coffee beans.